Analysis of The Relationship of Physical Activity Level to The Dementia: Literature Review - Pertiwi, Arum Setya; Sulistyani, S (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: dementia is a medical condition where there is a decrease in a person's cognitive abilities compared to the previous few months or years. People with dementia experience various types of cognitive difficulties, such as memory, language, attention, orientation, judgment, and planning. Increasing age substantially increases the risk of developing dementia. Apart from age, there are also lifestyle factors that can reduce or increase a person's risk of developing dementia. Approximately 35% of dementia is caused by a combination of 9 risk factors: low education level, hypertension, obesity, hearing loss, depression, diabetes, smoking, social isolation, and low physical activity. Objective: To determine the relationship between the level of physical activity and the incidence of dementia. Methods: This study was written as a literature review with a narrative analysis method using databases including Google Scholar, Pubmed, Science Direct. Data search was done using the keyword “Activity Daily Living” OR “Living Daily Activity” OR “Physical Activity” AND “Dementia” OR “Alzheimer Disease”. Results: At the article collection stage, 1.290 titles were obtained from 3 search engines. After screening, the authors found 15 articles that discussed the relationship between levels of physical activity and the incidence of dementia. The authors obtained 5 studies using non-dementia subjects and 10 studies using dementia subjects. Research with non-dementia subjects (before patients develop dementia) shows that physical activity can reduce the risk of dementia. Physical activity training and ADL (Activity Daily Living) in patients with MCI and dementia can increase ADL independence, balance, cognitive function, reduce sleep disorders and depression. Conclusion: there is a relationship between the level of physical activity with the incidence of dementia. High levels of physical activity can reduce the risk of developing dementia in the elderly.